Ferrocene containing polyaromatic hydrocarbons and the formation of a discotic nitrogen-heterosuperbenzene - Roberts, Dilwyn John (Trinity College (Dublin, Ireland). School of Chemistry, 2009)
Chapter 1 describes the synthesis and characterisation of a series of novel ferrocene containing polyphenylene compounds. These consist of polyphenylene molecules containing one, two, four and six ferrocene moieties. Also described is the formation of the first hexa-peri-benzocoronene (HBC) supporting a fully conjugated ferrocene moiety. UV-vis spectroscopy results indicate that the cyclopentadienyl rings of the ferrocenyl units tilt to differing degrees and this has consequences for subsequent cyclodehydrogenation attempts. The HBC supporting a fully conjugated ferrocene moiety undergoes an anodic shift in its redox potential when compared to ferrocene signifying the electron-withdrawing nature of the HBC.
Keywords: Chemistry, Ph.D.; Ph.D. Trinity College Dublin.